Empowerment of Gorontalo Local Natural Ingredients to Become Functional Food at Dasa Wisma, South Toto Village, Kabila District, Towards A Resilient Village in The Middle of COVID-19 - Hartati Hartati; Nangsih Sulastri Slamet; Arlan K. Imran; Salman Salman (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
COVID-19 is a global health problem, including in Indonesia. In addition to health problems, the increase in the number of cases of COVID-19 also has an impact on the global economy which affects stability in Indonesia. Based on the latest situation data on the development of COVID-19 cases released by the Task Force for the Acceleration of Handling COVID-19, Bone Bolango Regency, Gorontalo Province until December 31, 2020, Kabila District had the highest number of incidents, which had 122 positive confirmed cases of COVID-19. One of the 12 villages within the Kabila sub-district, South Toto Village had the highest incidence which had 38 cases. This community service aims to apply the results of research related to the use of natural materials such us Water Gourds(Lagenaria siceraria) which has antioxidant activity, so it can be used as an immunomodulator that can strengthen the body's resistance during the COVID-19 pandemic. The methods used were the distribution of Water Gourd juice syrup and training of cadres/community groups regarding the procedures for making Water Gourd juice syrup (Lagenaria siceraria). This is to increase the level of health and skills of the Gorontalo community in general and the awareness of cadres/community groups in the location where community service is carried out in particular. The parameters that can be measured in this community service are data from the pretest and posttest results which include questions related to public knowledge about COVID-19, Gorontalo local natural ingredients that are nutritious, knowledge in making functional drinks, as well as the rules and procedures for managing p-IRT for food processing businesses. Based on the results of data analysis, it was found that the average level of public knowledge increased from 58% to 72.4%.